An Academic Coaching Training Program for University Professionals: A Mixed Methods Examination. Issue 3 (27th May 2021) - Howlett, Marc Alan; McWilliams, Melissa A.; Rademacher, Kristen; Maitland, Theresa Laurie; O'Neill, J. Conor; Abels, Kimberly; Demetriou, Cynthia; Panter, Abigail
Abstract : Using an embedded mixed methods design, a randomized control trial assessed the effects of in-person and online academic coaching professional development training on university faculty and staff behaviors and attitudes with undergraduate students. Results suggest there was widespread implementation of academic coaching behaviors including collaboration, asking open-ended questions, and creating an action plan. While both in-person and online training formats produced positive changes for participants, the in-person training resulted in greater behavior adoption.